Dalam Bayang-bayang Maskulinitas: Studi Kasus Branding Politik Prabowo Subianto - Wahyu Triyogo Asbari; Edi Suwiknyo Suwiknyo; Eddi Kurnianto Saptawan Saptawan; M. Zacky Al Hosen Hosen (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2023)
Prabowo will run again as a presidential candidate in the 2024 presidential election. However, the 2024 presidential election is different from the previous elections. So far, Prabowo often uses visual displays that emphasize masculinity, such as firmness, courage and courage. It turned out that Prabowo lost. In 2019, the support team tried to change Prabowo's image by launching a rebranding with the slogan